Creating Performing Arts to Promote Community Products that Reflects the Local Identity Pathum Thani Province - Boontonglek, Manoch; Rittibul, Pravit; Boonsong, Panurat; Orachun, Riswan; Soontranon, Chaovalit; Senamontree, Sawatha (Journal of Ecohumanism, 2024)
The research on Creating Performing Arts to Promote Community Products That Reflects the Local Identity Pathum Thani Province aims to 1) study the characteristics and forms of community products in Pathum Thani Province as Intangible Cultural Heritage (ICH) and 2) create performing arts that promote community products that reflect the local identity in Pathum Thani Province by using research tools consisting of studying and surveying data from academic documents, information media, fieldwork and surveying structured interviews, and the researcher's experience. The obtained data were analyzed and synthesized in terms of content and triangulated data, and the performance results were evaluated using statistics and averages and standard deviations, and presented descriptively. Performing arts works were designed to be explained through the dimensions of performing arts. The findings reveal that Pathum Thani Province has integrated multiculturalism into the charm of the ancient community lifestyle. From the history of different ethnic groups, they have immigrated to live their lives from the past to the present. There have been developments in various types of community products, such as food products, agricultural products, household items, and souvenirs for tourism. In addition, there are traces of local cultural heritage reflecting history and way of life. There are important archaeological cultural sites, as well as activities reflecting the way of life. Local wisdom, customs, and unique cultures of the Mon Thai people that have been passed down have been used to develop creative forms that can be classified according to the 8 components of performing arts: 1) Performance design, 2) Performer selection, 3) Choreography design of performing arts, 4) Design of performing equipment, 5) Sound and music design, 6) Costume design, 7) Lighting design, and 8) Performance space design. In addition, the researcher has taken into account the concepts obtained after creating 3 classical dance arts: 1) Consideration of creativity in performing arts, 2) Consideration of the use of symbols in creating performing arts, and 3) Consideration of performing arts theory, music, and visual arts. This is also a collection of performing arts knowledge to integrate with other branches of knowledge, which is an academic advancement in creating performing arts works, as well as a guideline for further development and development of performing arts works in the future.